Conversation and Control: Emergent Progressive Pedagogy in the Last of Nebraska's One-Teacher Schools - Stephen A. Swindler (Journal of Research in Rural Education, 2005)
This article describes the teaching practices at Upper Rill School, a 1-teacher school in rural Nebraska. With its 8 students, grades 1 through 8, the teacher considers the school's size and continuity of student enrollment flexible and generative. Subject matter and grade levels are regularly integrated though common curricula. Instruction is carried out in conversations with individual students and in same- and mixed-grade groups. The pedagogy at Upper Rill has emergent qualities of progressive instruction, reflecting the ambitious teaching reformers call for. Small-scale schooling arguably enables a teacher to enact this kind of pedagogy.